Pelatihan E-Commerce untuk Pemula pada Sekolah Menengah Kejuruan Negeri 1 Cikarang - Danny, Muhtajuddin; Muhidin, Asep; Mulyana, Iwan; Hutauruk, Basar Maringan (VINICHO MEDIA PUBLISINDO, 2025)
This community service activity aims to provide basic training on using e-commerce platforms to students at State Vocational High School 1 Cikarang. This training is motivated by the need for digital literacy and entrepreneurship in the digital economy era, particularly for vocational high school students who are geared towards becoming work-ready workers or young entrepreneurs. The activity was implemented face-to-face through material delivery, live demonstrations on the use of e-commerce platforms such as Tokopedia and Shopee, as well as account creation and product marketing simulations. The results of this activity demonstrated an increased understanding of the students' basic e-commerce concepts, how to create an online store, and effective digital marketing strategies. This activity also stimulated students' interest in trying online entrepreneurship. It is hoped that this training will provide students with the initial foundation for utilizing digital technology for productive economic activities in the future.